CHARACTERIZATION AND DFN MODELLING OF THE FRACTURE NETWORK IN A MESOZOIC KARST RESERVOIR: GOMBA OILFIELD, PALEOGENE BASIN, CENTRAL HUNGARY. (July 2017) - Bauer, M.; Tóth, T. M.
Abstract : Reservoir rocks at Gomba oilfield, located in the Hungarian Paleogene Basin, include fractured and karstified Triassic carbonates with significant fluid storage potential. However little information is available about the fracture network in these carbonates which has led to production problems at Gomba. The purpose of this study is to investigate the relationship between the spatial distribution of high porosity zones in the carbonates and the microfracture system. For this evaluation, individual fractures were studied and used in a discrete fracture network (DFN) modelling exercise at two wells, Gomba‐1 and Gomba‐3. The investigation took place at two different scales. Fracture length and aperture distributions were derived at the micro‐scale (mm to cm), whereas fracture density and fracture orientation data were investigated at the reservoir scale. The results of both investigations were taken into consideration in the modelling. The results of the fracture network models were compared to reservoir lithologies which ranged from fractured carbonates to collapse breccias. Based on the results, it appears that the porosity associated with a significant proportion of the fractures was increased as a result of dissolution. Fracture distribution was not uniform along the studied well paths, and fracture orientation was chaotic at particular depth intervals. On the basis of the DFN models, three different fractured zones are predicted to occur in the reservoir, but only two of the zones have significant fracture porosity. Comparing these results with petrographic observations, an epigene karst phase is proposed which is older than (or the same age as) the time of hydrocarbon migration; karst‐related voids were therefore important pathways for fluid migration. The void system and karst caverns partly collapsed during subsequent burial, resulting in karst‐related traps. By analogy with modern cave systems, the karst cavern zones at Gomba probably extend horizontally rather than vertically, and are oriented NE‐SW parallel to major structural lineaments.